READING YOUTH ALIENATION AND MORAL TURMOIL IN AVENGED SEVENFOLD’S CITY OF EVIL (2005) - A. Fahmi Dahlan (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2026)
Avenged Sevenfold's City of Evil (2005) stands out as a unique cultural text that captures the intense emotional chaos and cultural uncertainty of American youth in the mid-2000s. This study aims to examine how youth alienation and moral turmoil are lyrically constructed in City of Evil, and to explain what this construction reveals about the sociocultural anxieties of mid-2000s American youth. Using a textual analysis of the album's lyrics, the study traces how alienation and moral turmoil are built through recurrent imagery of violence, displacement, betrayal, and existential strain. The analysis reveals that these lyrical patterns articulate a profound crisis of identity rooted in the anxieties of post-9/11 American consciousness, where notions of authority and purpose were destabilized. Crucially, the lyrics situate personal struggles—such as grief, addiction, and rage—not as purely individual problems, but as reflections of wider sociocultural tensions and national uncertainty. Ultimately, City of Evil is shown to mediate the fragile boundary between rebellion and resignation, demonstrating how contemporary metal encodes and expresses youth alienation as both an intimate emotional struggle and a symptom of collective cultural fracture.